A flood resilience assessment method of green-grey-blue coupled urban drainage system considering backwater effects - Liu, Yue; Zhang, Xiang; Liu, Jie; Wang, Yao; Jia, Haifeng; Tao, Shiyong (Ecological indicators, 2025)
[Display omitted] •The backwater effect index was introduced into the global resilience analysis method to improve accuracy.•The impact of green-grey-blue infrastructure on flood resilience has been studied.•The important role of backwater effects of blue infrastructure in flood resilience was quantified. Currently, the increasing frequency of urban floods—driven by extreme rainfall resulting from climate change, human-induced urbanization, and inadequacies in urban drainage systems—has heightened interest in resilient cities. Among these approaches, green-grey-blue coupling measures have emerged as one of the prominent technical solutions. Several studies have demonstrated the effectiveness of blue-green infrastructure and integrated green-grey-blue systems in mitigating flood disasters. However, a comprehensive assessment of the effectiveness of green-grey-blue infrastructure in enhancing urban flood resilience remains insufficient. This paper proposes an improved global resilience analysis (GRA) method to quantify the effectiveness of green-grey-blue infrastructure in flood resilience and the feedback relationships between influencing factors. The method offers a way to quantify the backwater effect of blue infrastructure in conditions where hydrological and hydraulic models cannot efficiently simulate the situation, by introducing the Potential Flooding Area Ratio (PFAR). The effectiveness of this method was further demonstrated in a typical watershed in Wuhan, China. The results show that green infrastructure is sufficient to handle rainfall with a return period of 5 years, with Low Impact Development (LID) facilities (green roof, permeable pavement and rain garden) outperforming Natural Green Space (NGS), but the difference decreases with increasing rain intensity. While the extension of the rainfall return period exacerbates urban flooding, even under the precipitation scenario associated with a 1,000-year return period, increasing pipe diameter can significantly enhance the flood resilience of grey infrastructure. The potential contribution of blue infrastructure to flood resilience is considerable, and optimized regulation schemes for the pre-flood water levels can enhance the adaptability of the system. It is worth noting that ignoring the backwater effect can lead to an overestimation of flood resilience assessment by up to 104 %, therefore, the introduction of PFAR has improved the accuracy of the assessment method by considering the convenience and efficiency of the model. The introduced backwater effect index incorporates the flooded area into the failure mode, filling the gap of traditional GRA method that only considers the flood volume and time, to help quantify the structural impact of green-grey-blue system on flood resilience.